Revealing the Potential of Lipid and β-Glucans Coproduction in Basidiomycetes Yeast - Byrtusová, Dana; Shapaval, Volha; Holub, Jiří; Šimanský, Samuel; Rapta, Marek; Szotkowski, Martin; Kohler, Achim; Márová, Ivana (Microorganisms, 2020)
Beta (β)-glucans are polysaccharides composed of D-glucose monomers. Nowadays, β-glucans are gaining attention due to their attractive immunomodulatory biological activities, which can be utilized in pharmaceutical or food supplementation industries. Some carotenogenic Basidiomycetes yeasts, previously explored for lipid and carotenoid coproduction, could potentially coproduce a significant amount of β-glucans. In the present study, we screened eleven Basidiomycetes for the coproduction of lipids and β-glucans. We examined the effect of four different C/N ratios and eight different osmolarity conditions on the coproduction of lipids and β-glucans. A high-throughput screening approach employing microcultivation in microtiter plates, Fourier Transform Infrared (FTIR) spectroscopy and reference analysis was utilized in the study. Yeast strains C. infirmominiatum CCY 17-18-4 and R. kratochvilovae CCY 20-2-26 were identified as the best coproducers of lipids and β-glucans. In addition, C. infirmominiatum CCY 17-18-4, R. kratochvilovae CCY 20-2-26 and P. rhodozyma CCY 77-1-1 were identified as the best alternative producers of β-glucans. Increased C/N ratio led to increased biomass, lipid and β-glucans production for several yeast strains. Increased osmolarity had a negative effect on biomass and lipid production while the β-glucan production was positively affected.
Keywords: carbon:nitrogen ratio; high-throughput screening; osmotic stress; lipids; red yeast; β-glucans